Penguatan Nilai-Nilai Budi Pekerti Melalui Kitab Ngudi Susilo Bagi Anak-Anak di Desa Rogodadi Kabupaten Kebumen Berbasis Participatory Action Research (PAR) - Fatimah, Siti; Agus Salim, Muhammad; Achid Nurseha, Muhammad; Subarkah, Imam; Apriliani, Titi; Tajriyaan Rafik, Aynaani; Anjali, Lia; Lestari, Fiji; Priyatno, Riski; Zidni Al Mubarok, Akhmad; Dwi Cahyaningrum, Septiana (BALE LITERASI, 2023)
This service aims to strengthen the values of character for children in Rogodadi Village, Kebumen Regency. This assistance was carried out for 1 month with 9 meetings. The participants in this assistance were 15 children in Rogodadi Village, Buayan District, Kebumen Regency. The implementation method uses the PAR (Participatory Action Research) method with five stages, namely: Diagnosis, Action Planning, Action Taking, Evaluation, and Specifying Learning. Data collection techniques using observation, interviews, and documentation. The results of the activity show that the activity of strengthening moral values through the Kitab Ngudi Susilo has been successfully implemented. The results of the analysis during the activity, the children understand well and can implement the manners that must be carried out by a child. Some of the methods used in this strengthening activity include CTL model, demonstrations, and interactive lectures. Having a daily journal given to children is a measure of the success of this activity. The results of the analysis of daily journals found that children can implement manners by Kitab Ngudi Susilo. The results of the questionnaire also showed that as many as 94% of the children understood the material presented by the service team well.